The Differences and Similarities of Preposition Patterns in Batak Toba and English Language through Narrative Text: A Contrastive Analysis - Suryani Sinaga; Sintia Tampubolon; Angelica Napitupulu; Herman; Ridwin Purba; Junita Batubara; Suhono, Suhono (Anglophile Journal, 2024)
This study examines the differences and similarities in prepositional patterns between Batak Toba and English languages through a contrastive analysis of narrative texts. The phenomenon in focus is the variation in preposition usage between these two languages, which often poses difficulties for native Batak Toba speakers learning English. The objective of this research is to identify and compare prepositional patterns in both languages and analyzes their implications for English language learning among Batak Toba speakers. The method employed is a qualitative contrastive analysis with a descriptive approach. Data was obtained from three pairs of equivalent narrative texts in English and Batak Toba. The results reveal significant differences in the use of spatial and temporal prepositions, as well as some similarities in prepositions indicating abstract relationships. The main difference lies in the greater number and variety of prepositions in English, while Batak Toba tends to use simpler and more limited prepositions. The implications of this research provide valuable insights for developing effective English language learning strategies for Batak Toba speakers, considering positive and negative transfer between the two languages.